2018
DOI: 10.1101/474346
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How does cilium length affect beating?

Abstract: The effects of cilium length on the dynamics of cilia motion were investigated by high-speed video microscopy of uniciliate mutants of the swimming alga, Chlamydomonas reinhardtii. Cells with short cilia were obtained by deciliating cells via pH shock and allowing cilia to reassemble for limited times.The frequency of cilia beating was estimated from motion of the cell body and of the cilium. Key features of the ciliary waveform were quantified from polynomial curves fitted to the cilium in each image frame. M… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 66 publications
2
13
0
Order By: Relevance
“…6.24±1.26μm), providing at least a partial basis for ciliary transport failure based on biophysical models for mucociliary transport which include ciliary length as a critical parameter in force generation [26][27][28] .…”
mentioning
confidence: 99%
“…6.24±1.26μm), providing at least a partial basis for ciliary transport failure based on biophysical models for mucociliary transport which include ciliary length as a critical parameter in force generation [26][27][28] .…”
mentioning
confidence: 99%
“…Fifty movies of fap57-050; uni1 and 51 movies of fap57-706; uni1 were compared to 153 movies of uni1-2 (the wild-type group was previously described by Bottier et al . [ 71 ]) ( Fig 5A , S6 Fig ). Body motion analysis shows that both mutants have a significantly slower body rotation rate compared to wild-type cells ( Fig 5C ), which agrees with the reduced velocity.…”
Section: Resultsmentioning
confidence: 99%
“…The single mutant uni1 is considered the wild-type reference as previously published [ 70 ]. Videos were analyzed using a custom-made program written in Matlab R2016a (The Mathworks, Natick, MA, USA) previously published [ 71 ]. From each video, a sequence of 200 consecutive frames was stored in a 3D matrix of pixel intensity values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that WDPCP governs ciliogenesis in Xenopus embryos [14,17] and human nasal epithelium [18]. Although short cilia might contribute to cilia beating dysfunction [30], it is still unclear whether WDPCP directly regulated the beating of cilia. To our knowledge, this is the first study of WDPCP on cilia function in human sinonasal epithelium.…”
Section: Discussionmentioning
confidence: 99%